Conversion of sustainable agricultural residues into MCC for PLA-based biodegradable plastic applications - Thi Thu Ha Vu; Thi Bay Nguyen; Thanh Trung Nguyen; Nam Phong Pham; Van Bac Pham; Thi Thu Trang Nguyen (Petrovietnam Journal, 2025)
Microcrystalline cellulose (MCC) was extracted from cassava stems, banana pseudostems, pineapple leaves, and spent coffee grounds through an optimized acid hydrolysis process. Comprehensive structural, morphological, and thermal characterization revealed distinct differences among sources, with cassava stem-derived MCC identified as the most feasible and sustainable option due to its high crystallinity, uniform particle size, processing stability, ready availability, and large-scale supplypotential. This MCC was incorporated into thermoplastic starch (TPS) and polylactic acid (PLA) matrices to fabricate fully biodegradable composites. X-ray diffraction (XRD) confirmed the preservation of MCC crystalline structure, scanning electron microscopy (SEM) revealed homogeneous dispersion within the TPS phase, and thermogravimetric/differential thermal analyses (TGA/DTA) demonstrated improved thermal stability. Mechanical testing showed that the optimized PLA:MCC:TPS ratio of 70:4.5:25.5 (with 15% MCC relative to (MCC/TPS)) provided the best balance between tensile strength, modulus, and biodegradability.These composites exhibited mechanical strength for sustainable packaging and food service applications while maintaining full compostability. Overall, the results highlight cassava stems as a sustainable, locally available MCC source and confirm that PLA/(MCC/TPS) composites can replace petrochemical-based plastics in targeted sectors, contributing to global energy transition strategies and CO2 emission reduction targets.